Cover Image. Issue 1 (21st January 2019) - Murgia, Manuela; Fiamma, Maura; Barac, Aleksandra; Deligios, Massimo; Mazzarello, Vittorio; Paglietti, Bianca; Cappuccinelli, Pietro; Al‐Qahtani, Ahmed; Squartini, Andrea; Rubino, Salvatore; Al‐Ahdal, Mohammed N.
Abstract : The cover image is based on the Original Research Biodiversity of fungi in hot desert sands by Manuela Murgia et al., DOI:10.1002/mbo3.595 .